Effects of learning styles and time management on academic achievement - Indreica Elena-Simona; Cazan Ana-Maria; Truța Camelia (My University, 2011)
The present paper presents an experiment conducted between November 2009 and February 2011. The main hypothesis of the study was that efficient time management, under the guidance of an educational counselor, lead to significant increases in students academic performances and, consequently, lead to academic success. A number of 130 participants with low academic performances after the first two semesters (October 2009 – February 2010 – First semester, March – June 2010 – The second semester) participated in the study. All participants had above average or superior intellectual abilities (according to baccalaureate results). The educational counselor elaborated individualized and flexible programs for each participant in the experimental condition according to students learning styles, circadian, and eating rhythms, and daily and weekly effort curves. The program included planning of all activities participants were to develop during the two months of the experimental intervention. The results confirmed the hypothesis, showing the efficiency of time management individualized programs.
Keywords: Time management; learning styles; academic succes